GENDER PERSPECTIVE IN THE QUR'AN: A THEMATIC AND ANALYTICAL STUDY OF EQUALITY AND ROLES - Natsir, Imron (Takafu: Journal of Tafsir and Gender Perspective, 2025)
This study explores the gender perspective within the Qur'an, emphasizing its stance on equality, roles, and responsibilities of men and women in various spheres of life. While gender discourse in Islam has often been shaped by cultural and historical interpretations, the Qur'an provides foundational texts that assert both spiritual and moral equality of the sexes. Through a thematic and analytical review of key verses, this paper investigates Qur'anic narratives concerning creation, leadership, inheritance, education, and social justice. The study critically engages with both classical and contemporary interpretations, highlighting the implications of Qur'anic gender principles in modern contexts, particularly in relation to women's rights, empowerment, and gender justice. Employing a qualitative methodology grounded in tafsir literature and feminist hermeneutics, this paper contributes to a more holistic and balanced understanding of gender in Islamic thought. The findings suggest that the Qur'an advocates for gender equity rooted in taqwa (piety), rather than biological determinism, and calls for continuous engagement with divine texts in light of evolving societal realities.